Undergraduate studies in Journalism. Ten proposals of scientific research for future professionals - Cartes-Barroso, Manuel J.; Ufarte-Ruiz, María-José; Murcia-Verdú, Francisco-José (Infonomy, 2024)
Undergraduate studies in Journalism have envolved notably in Spain since the creation of the first Faculties of Information Sciences in the 1970’s. But not always at the same pace as the journalistic profession and industry. With constant technological innovation, the boom that this sector has experienced in recent years has widened the gap between universities and companies, because Journalism training does not follow in his footsteps with the same speed. It is therefore necessary to update the curricula of Journalism and Communication degrees in order to train journalists, considering all the transformations and new professional profiles that media and news companies need. This contribution synthesises ten proposals from scientific research focusing on technologies, digitalisation and journalistic innovation, whose authors propose adapting the university education in Journalism to the real needs of the labour market. It is a difficult and time-consuming task to achieve, above all.